2010
DOI: 10.1021/ic100051j
|View full text |Cite
|
Sign up to set email alerts
|

Corrections to Toward Unidirectional Rotary Motion in Nickelacarboranes: Characterization of Diastereomeric Nickel Bis(Dicarbollide) Complexes Derived from the [Nido-7-CH3-7,8-C2B9H11] Anion

Abstract: In column 1, line 12, it should be "through" rather than "thorough"; in column 1, line 31, it should be 11.42(6)°rather than 11.48(4)°; in column 2, line 3, it should be 1.4939(7) and 1.4937(7) A ˚rather than 1.4946(2) and 1.4939(2) A ˚.Page 9382. In Table 2, column 5, row 6, for compound Ni III (6), the distance 2.152(1) for Ni-C1A is incorrectly presented in bold; in column 8, row 12, for compound NMe 4 3 4, the distance 2.268(2) for Ni-C 2 B should be in bold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This distortion has been attributed to both the electron richness of the system and the ligand asymmetry, so it could be much less achievable in the highly symmetric metallocenes. Besides the slipped-sandwich structure, cisoid and transoid conformations have been presented by Hawthorne et al 106,107 and described by the same author 108,109 and by Nuńẽz et al 102 Intermediate gauche conformations may also be observed. 102 Undoubtedly, this is not just a matter of steric hindrance, since the cisoid conformation is preferred by d 6 Ni(IV) and Pd(IV) ions and the electronic distribution plays a key role 102 together with the intermolecular interactions and the anion environment.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…This distortion has been attributed to both the electron richness of the system and the ligand asymmetry, so it could be much less achievable in the highly symmetric metallocenes. Besides the slipped-sandwich structure, cisoid and transoid conformations have been presented by Hawthorne et al 106,107 and described by the same author 108,109 and by Nuńẽz et al 102 Intermediate gauche conformations may also be observed. 102 Undoubtedly, this is not just a matter of steric hindrance, since the cisoid conformation is preferred by d 6 Ni(IV) and Pd(IV) ions and the electronic distribution plays a key role 102 together with the intermolecular interactions and the anion environment.…”
Section: Chemical Reviewsmentioning
confidence: 99%